The influence of range of motion on the functional and structural capacity of the triceps brachii—an experimental study with electromyography - Luís M. Ferreira; Luís Ferreira; Joana Ribeiro; Luís Branquinho; Rafael Peixoto; Luciano Bernardes Leite; Pedro Forte (AIMS Biophysics)
Range of motion in exercises is one of the foundations for greater activation of a muscle group. The objective of this investigation was to compare the structural and functional capacity of the triceps brachii between three groups with different angles (90°, 110°, and 130°) in a unilateral elbow extension exercise. The sample consisted of 25 subjects with a mean age of 24.12 ± 3.83 years, mean height of 1.78 ± 0.10 m and mean body weight of 78.01 ± 15.70 kg. The following variables were collected pre- and post-intervention: triceps brachii circumference, one repetition maximum, and electromyography during dynamic exercise. Over eight weeks, subjects performed this exercise, performing 3 sets of 12 repetitions for each arm, with days of rest in between. The results showed that the 110° angle provided greater muscle activation compared to the other angles. There was no difference between the triceps brachii circumference and the root mean square (RMS) between the groups. It was concluded that, although the 110° angle showed a tendency for greater muscle activation, the RMS and arm perimeter data did not show significant differences between all the angles evaluated (90°, 110°, 130°).